The Health Impact Fund: making the case for engagement with pharmaceutical laboratories in Brazil, Russia, India, and China - Vivian Chia-Jou Lee; Jacqueline Yao; William Zhang (Globalization and Health, 2021)
Abstract Despite progress in global health, the general disease burden still disproportionately falls on low- and middle-income countries. The health needs of these countries’ populations are unmet because there is a shortage in drug research and development, as well as a lack of access to essential drugs. This health disparity is especially problematic for diseases associated with poverty, namely neglected tropical diseases and microbial infections. Currently, the pharmaceutical landscape focuses on innovations determined by profit margins and intellectual property protection. To expand drug accessibility and catalyze research and development for neglected diseases, a team of researchers proposed the Health Impact Fund as a potential solution. However, the fund is predominantly considering partnerships with pharmaceutical giants in high-income countries. This commentary explores the limitations and benefits in partnering with pharmaceutical companies based in Brazil, Russia, India, and China (BRIC), with the goal of expanding the Health Impact Fund’s vision to incorporate long-term, local partnerships. Identified limitations to a BRIC country partnership include lower levels of drug development expertise compared to their high-income pharmaceutical counterparts, and whether the Health Impact Fund and the participating stakeholders have the financial capability to assist in bringing a new drug to market. However, potential benefits include the creation of new incentives to fuel competitive local innovation, more equitable routes to drug discovery and development, and a product pipeline that could involve stakeholders in lower- and middle-income countries. Our commentary explores how partnership with pharmaceutical firms in BRIC countries might be advantageous for all: The Health Impact Fund, pharmaceutical companies in BRIC economies, and stakeholders in low- and middle- income countries.